O trabalho pedagógico para e com as infâncias em situação de vulnerabilidade social: projetos colaborativos em construção - Vivian, Darlane Marques (2023)
This study is linked to the Professional Master's Course, of the Postgraduate Program in Public Policies and Educational Management, in the Research Line LP2 Pedagogical Management and Educational Contexts, its theme is Management of pedagogical work for and with children through collaborative projects in a school that serves a socially vulnerable community. The objective was to collectively build possibilities for collaborative management of pedagogical work for and with children based on reflections on projects developed in an institution that serves communities in situations of social vulnerability. The specific objectives were prioritized: recognizing the projects developed in pedagogical work for and with children during remote education (2020 and 2021); identify the learning mobilized by teachers in the development of projects during remote teaching (2020 and 2021); understand the relationship between projects developed during the pandemic period and the collaborative management of pedagogical work for and with children; collaboratively construct a chapter of the school's Pedagogical Political Project on pedagogical work based on projects for and with children. The research is of a qualitative narrative nature of a sociocultural nature (BOLZAN, 2001) developed from dialogical meetings based on the approach of listening, contextualization, experience and re-elaboration (POWACZUK et al., 2021). The locus of the research was a school that serves a community in a situation of social vulnerability, with the participation of teachers working in Early Childhood Education and Early Years, as well as the management team. The study made it possible to identify the management of pedagogical work for/with children based on three categorical dimensions: collaborative projects under construction; teaching learning; perspectives in rebuilding collaborative projects. The projects at Escola Municipal de Ensino Fundamental Júlio do Canto were empowering in a challenging period for humanity, which was the Covid-19 pandemic and remote teaching, and together brought possibilities for a reconfiguration of pedagogical work , through collaborative projects, permeated by critical reflections and collective constructions of significant proposals and actions for a community that also suffered from physical isolation, the precariousness of digital resources and the lack of minimum conditions for survival. The educational product presented is a chapter for the school's Pedagogical Political Project, prepared together with the group of teachers who have articulated, thought about and developed collaborative projects at the institution.